2023
DOI: 10.1101/2023.03.01.530610
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Uncovering and exploiting the return of voluntary motor programs after paralysis using a bi-cortical neuroprosthesis

Abstract: Rehabilitative and neuroprosthetic approaches after spinal cord injury (SCI) aim to reestablish voluntary control of movement. Promoting recovery requires a mechanistic understanding of the return of volition over action, but the relationship between re-emerging cortical commands and the return of locomotion is not well established. We introduced a neuroprosthesis delivering targeted bi-cortical stimulation in a clinically relevant contusive SCI model. In healthy and SCI cats, we controlled hindlimb locomotor … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 84 publications
(47 reference statements)
0
2
0
Order By: Relevance
“…These findings, in addition to shedding light on the intricate ipsilateral control of movement in rats, carry promising translational implications for the future development of neuroprosthetic solutions. Our previous work has demonstrated that phase-dependent cortical stimulation applied to the contralesional motor cortex immediately ameliorates dragging deficits following SCI by specifically enhancing contralateral hindlimb flexion (Bonizzato & Martinez, 2021 ;Duguay et al, 2023 ). Given that ipsilesional cortical stimulation induces a bilateral synergy, leading to the improvement of the affected limb's extension, this approach has the potential to effectively complement contralesional cortical stimulation.…”
Section: Cortical Neuroprosthesesmentioning
confidence: 99%
See 1 more Smart Citation
“…These findings, in addition to shedding light on the intricate ipsilateral control of movement in rats, carry promising translational implications for the future development of neuroprosthetic solutions. Our previous work has demonstrated that phase-dependent cortical stimulation applied to the contralesional motor cortex immediately ameliorates dragging deficits following SCI by specifically enhancing contralateral hindlimb flexion (Bonizzato & Martinez, 2021 ;Duguay et al, 2023 ). Given that ipsilesional cortical stimulation induces a bilateral synergy, leading to the improvement of the affected limb's extension, this approach has the potential to effectively complement contralesional cortical stimulation.…”
Section: Cortical Neuroprosthesesmentioning
confidence: 99%
“…The relationship between cortical commands and locomotion has received attention in the last decades (Amboni, Barone, & Hausdorff, 2013 ). In recent studies, we have shown that, after a unilateral spinal cord injury in rats (Bonizzato & Martinez, 2021 ) and large spinal contusion injuries in cats (Duguay et al, 2023 ), microstimulation delivered to the contralesional motor cortex in phase coherence with locomotion immediately alleviated contralateral hindlimb deficits. Other studies have shown that not only the cortex proactively controls high-level and goal-oriented motor planning but it is also involved during stereotyped locomotion (Artoni et al, 2017 ;Bretzner & Drew, 2005 ;Song & Giszter, 2011 ;Song et al, 2009 ).…”
Section: Introductionmentioning
confidence: 98%
“…These findings, in addition to shedding light on the intricate ipsilateral control of movement in rats, carry promising translational implications for the future development of neuroprosthetic solutions. Our previous work has demonstrated that phasedependent cortical stimulation applied to the contralesional motor cortex immediately ameliorates dragging deficits following SCI by specifically enhancing contralateral hindlimb flexion (Bonizzato & Martinez, 2021;Duguay et al, 2023). Given that ipsilesional cortical stimulation induces a bilateral synergy, leading to the improvement of the affected limb's extension, this approach has the potential to effectively complement contralesional cortical stimulation.…”
Section: Cortical Neuroprosthesesmentioning
confidence: 99%
“…The relationship between cortical commands and locomotion has received attention in the last decades (Amboni, Barone, & Hausdorff, 2013). In recent studies, we have shown that, after a unilateral spinal cord injury in rats (Bonizzato & Martinez, 2021) and large spinal contusion injuries in cats (Duguay et al, 2023), microstimulation delivered to the contralesional motor cortex in phase coherence with locomotion immediately alleviated contralateral hindlimb deficits.…”
Section: Introductionmentioning
confidence: 98%
“…The relationship between cortical commands and locomotion has received attention in the last decades (Amboni, Barone, & Hausdorff, 2013 ). In recent studies, we have shown that, after a unilateral spinal cord injury in rats (Bonizzato & Martinez, 2021 ) and large spinal contusion injuries in cats (Duguay et al, 2023 ), microstimulation delivered to the contralesional motor cortex in phase coherence with locomotion immediately alleviated contralateral hindlimb deficits. Other studies have shown that not only the cortex proactively controls high-level and goal-oriented motor planning but it is also involved during stereotyped locomotion (Artoni et al, 2017 ;Bretzner & Drew, 2005 ;Song & Giszter, 2011 ;Song et al, 2009 ).…”
Section: Introductionmentioning
confidence: 98%